Mitochondrial Translocation of High Mobility Group Box 1 Facilitates LIM Kinase 2-Mediated Programmed Necrotic Neuronal Death - Hyun, Hye-Won; Ko, Ah-Reum; Kang, Tae-Cheon (Frontiers in Cellular Neuroscience, 2016)
High mobility group box 1 (HMGB1) acts a signaling molecule regulating a wide range of inflammatory responses in extracellular space. HMGB1 also stabilizes nucleosomal structure and facilitates gene transcription. Under pathophysiological conditions, nuclear HMGB1 is immediately transported to the cytoplasm through chromosome region maintenance 1 (CRM1). Recently, we have reported that up-regulation of LIM kinase 2 (LIMK2) expression induces HMGB1 export from neuronal nuclei during status epilepticus (SE)-induced programmed neuronal necrosis in the rat hippocampus. Thus, we investigated whether HMGB1 involves LIMK2-mediated programmed neuronal necrosis, but such role is not reported. In the present study, SE was induced by pilocarpine in rats that were intracerebroventricularly infused with saline, control siRNA, LIM kinase 2 (LIMK2) siRNA or leptomycin B (LMB, a CRM1 inhibitor) prior to SE induction. Thereafter, we performed Fluoro-Jade B staining, western blots and immunohistochemical studies. LIMK2 knockdown effectively attenuated SE-induced neuronal death and HMGB1 import into mitochondria accompanied by inhibiting nuclear HMGB1 release and abnormal mitochondrial elongation. LMB alleviated SE-induced neuronal death and nuclear HMGB1 release. However, LMB did not prevent mitochondrial elongation induced by SE, but inhibited the HMGB1 import into mitochondria. The efficacy of LMB was less effective to attenuate SE-induced neuronal death than that of LIMK2 siRNA. These findings indicate that nuclear HMGB1 release and the subsequent mitochondrial import may facilitate and deteriorate programmed necrotic neuronal deaths. The present data suggest that the nuclear HMGB1 release via CRM1 may be a potential therapeutic target for the programmed necrotic neuronal death induced by SE.